2011
DOI: 10.1258/acb.2011.011106
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Quantum Blue® rapid test for faecal calprotectin

Abstract: Background: Calprotectin is an acute-phase protein used extensively in the assessment of gastrointestinal inflammation. It can readily be measured by enzyme-linked immunoassay (ELISA) and recently by point-of-care testing (POCT). We evaluated the Quantum Blue w POCT in this study and compared it with our existing ELISA method. Methods: The method comparison study used faecal samples (n ¼ 47) sent to the laboratory for routine calprotectin analysis. Linearity was assessed by serial dilution of extracted faeces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…Slopes of the regression curves varied from 1.0 to 2.24 and intercepts from -11 to -40. [9][10][11][12] Some of the variability in our study might have been caused by the different extraction devices and procedures, as was shown in the study of Whitehead et al 8 However, we also observed major quantitative differences between assays using the same extraction device.…”
Section: Discussionmentioning
confidence: 52%
“…Slopes of the regression curves varied from 1.0 to 2.24 and intercepts from -11 to -40. [9][10][11][12] Some of the variability in our study might have been caused by the different extraction devices and procedures, as was shown in the study of Whitehead et al 8 However, we also observed major quantitative differences between assays using the same extraction device.…”
Section: Discussionmentioning
confidence: 52%
“…The results of the fecal calprotectin test, having a point-ofcare testing (POCT) method, were read quantitatively using the Quantum Blue Reader. Values 50 mg/g and higher were considered as positive, per the manufacturer' s instructions [9]. The study was acknowledged by Sifa University Ethics Committee and funded by Sifa University Scientific Research Projects Unit.…”
Section: Methodsmentioning
confidence: 99%
“…Wassell et al 95 compared Quantum Blue POCT against PhiCal ELISA in 47 samples sent to the laboratory for 'routine calprotectin analysis'. They tested three extractions of the same stool in three patients and found considerable variation: results varied from -31.3% to 31.5%.…”
Section: Wassell 2012mentioning
confidence: 99%